Comparison of the differentiation of dental pulp stem cells and periodontal ligament stem cells into neuron-like cells and their effects on focal cerebral ischemia. (26th August 2020) - Wu, Tingting; Xu, Wanting; Chen, Hanlin; Li, Shasha; Dou, Rengang; Shen, Hongtao; Liu, Xue; Liu, Xiaoyu; Hong, Yongfeng; He, Jiacai
Abstract: Recent studies have reported an increasing incidence of ischemic stroke, particularly in younger age groups. Dental pulp stem cells (DPSCs) and periodontal ligament stem cells (PDLSCs) are the most common stem cells acquired from the teeth of adults, even elderly people. However, there are no detailed reports on whether DPSCs or PDLSCs are suitable for the treatment of ischemic stroke. In this study, the in vitro differentiation of DPSCs and PDLSCs into neuron-like cells was evaluated. Then, we established a rat model of cerebral ischemia. DPSCs or PDLSCs were administered to animals, and the therapeutic effects of these two types of cells were investigated. The results showed that PDLSCs had a higher differentiation rate than DPSCs. Immunofluorescence studies showed that the expression of the neuronal differentiation marker Thy-1 was higher in PDLSCs than in DPSCs, and other gene markers of neuronal differentiation showed corresponding trends, which were confirmed by western blot analysis. In this process, the Notch and Wnt signaling pathways were inhibited and activated, respectively. Finally, rats with transient occlusion of the right middle cerebral artery were used as a model to assess the therapeutic effect of PDLSCs and DPSCs on ischemia. The results showed that rats in the PDLSC-treated group emitted significantly greater red fluorescence signal than the DPSC-treated group. PDLSC transplantation promoted the recovery of neurological function more effectively than DPSC transplantation. Hence, PDLSCs represent an autogenous source of adult mesenchymal stem cells with desirable biological properties and may be an ideal candidate for clinical applications.